3D printing technique for the development of non‐planar electromagnetic bandgap structures for antenna applications. Issue 3 (1st February 2016) - Jun, S.; Sanz‐Izquierdo, B.; Parker, E.A.
Abstract : The use of 3D printing for the development of non‐planar electromagnetic bandgap (EBG) structures for antenna applications is proposed. A coplanar waveguide (CPW) fed antenna is tested on a non‐planar EBG substrate, fabricated using additive manufacturing techniques. Inexpensive fuse filament fabrication is used as the fabrication process. Silver‐loaded conducting ink is employed for the metallic components of the EBG. The CPW antenna on the non‐planar EBG structure has a satisfactory reflection coefficient at 2.45 GHz, which is suitable for Bluetooth/WLAN communications. The radiation patterns have reduced back lobes and improved gain compared with the antenna in free space.